Fabricating hydrogel for solar steam generation - Leow, Ming Zhe (Nanyang Technological University, 2021)
Solar vapour generation (SVG), the process of extracting vapor from liquid water by using the means of solar energy, has been an on-going research for many years. SVG is able to include the fundamentals of eco-friendly and cost-effective growth. Thus, there have been several experimental and theoretical studies performed, to focus on innovative photothermal materials and the means of having an effective evaporation rate. In this project, the author summarized the basic concepts of SVG, the latest trend of using interfacial SVG, as well as the science and design for efficient solar-to thermal energy conversion and vapour generation in this project. Furthermore, the author discusses on how to integrate photothermal materials into the primary material to boost the evaporation system's efficiency.